2014
DOI: 10.1128/jvi.02286-14
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mason-Pfizer Monkey Virus CA-NC Spacer Peptide-Like Domain in Assembly of Immature Particles

Abstract: The hexameric lattice of an immature retroviral particle consists of Gag polyprotein, which is the precursor of all viral structural proteins. Lentiviral and alpharetroviral Gag proteins contain a peptide sequence called the spacer peptide (SP), which is localized between the capsid (CA) and nucleocapsid (NC) domains. SP plays a critical role in intermolecular interactions during the assembly of immature particles of several retroviruses. Published models of supramolecular structures of immature particles sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 72 publications
0
21
0
Order By: Relevance
“…Finally, in the betaretrovirus Mason-Pfizer monkey virus (MPMV), there is only one cleavage between CA and NC. While the sequence of this region of Gag appears consistent with a helical conformation, careful studies found no evidence for a helix here (55). It is intriguing to note that a region of MPMV Gag on the N-terminal side of CA exhibits behavior somewhat analogous to that of HIV-1 SP1 (56).…”
Section: Fig 10mentioning
confidence: 99%
“…Finally, in the betaretrovirus Mason-Pfizer monkey virus (MPMV), there is only one cleavage between CA and NC. While the sequence of this region of Gag appears consistent with a helical conformation, careful studies found no evidence for a helix here (55). It is intriguing to note that a region of MPMV Gag on the N-terminal side of CA exhibits behavior somewhat analogous to that of HIV-1 SP1 (56).…”
Section: Fig 10mentioning
confidence: 99%
“…Nevertheless, the 12 and 13 amino acids of the CA C terminus and NC N terminus, respectively, were shown to play a critical role in the assembly of the immature particles (3,4). This part of the M-PMV Gag was therefore termed a spacer peptide-like domain (4). Similarly to M-PMV, gammaretroviruses have no spacer peptide between the CA and NC.…”
mentioning
confidence: 99%
“…In contrast, the betaretrovirus Mason-Pfizer monkey virus (M-PMV) has only one cleavage site between the CA and NC. Nevertheless, the 12 and 13 amino acids of the CA C terminus and NC N terminus, respectively, were shown to play a critical role in the assembly of the immature particles (3,4). This part of the M-PMV Gag was therefore termed a spacer peptide-like domain (4).…”
mentioning
confidence: 99%
“…The GPG mutant failed to form immature particles inside the cells; however, a large amount of electron-dense material (presumably Gag) accumulated underneath the cell plasma membrane (Fig. 6D) (55). This compact layer on the membrane did not form any released virus particles or budding structures.…”
Section: Resultsmentioning
confidence: 99%
“…In the GPG mutant, dense layers of accumulated protein are seen underlying the plasma membrane, which are not seen in noninfected cells. Based on the thickness of these layers, and because similar structures have previously been shown to be formed by assembly-incompetent Gag polyproteins (55,60,61), we presume that these extra layers observed under the plasma membrane are formed by accumulated mutant Gag protein.…”
Section: Discussionmentioning
confidence: 99%